Counterexamples on uniform convergence sequences, series, functions, and integrals - Bourchtein, Andrei; Bourchtein, Ludmila (Wiley, 2017)
This book presents counterexamples to false statements typically found within the study of mathematical analysis, real analysis, and calculus, all of which are related to infinite sequences, series of functions, and functions and integrals depending on a parameter.